2023
DOI: 10.1002/adhm.202300977
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Allyl‐Modified Gelatin Photoclick Resin Tailored for Volumetric Bioprinting of Matrices for Soft Tissue Engineering

Alessandro Cianciosi,
Sabrina Stecher,
Maxi Löffler
et al.

Abstract: Volumetric bioprinting (VBP) is a light‐based 3D printing platform, which recently prompted a paradigm shift for additive manufacturing (AM) techniques considering its capability to enable the fabrication of complex cell‐laden geometries in tens of seconds with high spatiotemporal control and pattern accuracy. A flexible allyl‐modified gelatin (gelAGE)‐based photoclick resin is developed in this study to fabricate matrices with exceptionally soft polymer networks (0.2–1.0 kPa). The gelAGE‐based resin formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Allyl-thiol step-growth cross-linking was recently exploited also by Ciancosi et al in a photoresin composed of allyl-gelatin (Gel-AGE) and thiolated PEG. 156 By tailoring the polymer content and the allyl to thiol ratio, the authors reported tomographic printing of exceptionally soft matrices (200−1000 Pa) in tens of seconds (20−50 s). Delicate, differentiated adipocytes were embedded in Gel-AGE based photoresin and printed with high viability (>90%) as proof-of-concept for tomographic bioprinting in the engineering of soft tissues such as brain, lung, breast and endothelial tissues.…”
Section: Step Growth Cross-linking For Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allyl-thiol step-growth cross-linking was recently exploited also by Ciancosi et al in a photoresin composed of allyl-gelatin (Gel-AGE) and thiolated PEG. 156 By tailoring the polymer content and the allyl to thiol ratio, the authors reported tomographic printing of exceptionally soft matrices (200−1000 Pa) in tens of seconds (20−50 s). Delicate, differentiated adipocytes were embedded in Gel-AGE based photoresin and printed with high viability (>90%) as proof-of-concept for tomographic bioprinting in the engineering of soft tissues such as brain, lung, breast and endothelial tissues.…”
Section: Step Growth Cross-linking For Biomedical Applicationsmentioning
confidence: 99%
“…Allyl-thiol step-growth cross-linking was recently exploited also by Ciancosi et al in a photoresin composed of allyl-gelatin (Gel-AGE) and thiolated PEG . By tailoring the polymer content and the allyl to thiol ratio, the authors reported tomographic printing of exceptionally soft matrices (200–1000 Pa) in tens of seconds (20–50 s).…”
Section: Applications Of Dvpmentioning
confidence: 99%
“…Furthermore, the thiol-ene reaction features a high reaction kinetic, oxygen insensitivity, compatibility with low concentration monomers, and limited hydrogel shrinking and polymerization stress 1315 . Allyl-modified gelatin (gelAGE) is an established biomaterial platform which undergoes thiol-ene click reaction in presence of a thiolated crosslinker and a photoinitiator (PI) 16,17 . VPP technologies often exploit resin formulations with photoabsorber (PA) to attenuate the light penetration depth and to withdraw photons from the PI, thus delaying the radical formation and yielding to more resolved features 18,19 .…”
Section: Introductionmentioning
confidence: 99%